Plasticity at the Dawn of Deep Learning. - Dougherty, Stephen (University of Toronto Quarterly, 2025)
This article explores Catherine Malabou's philosophical concepts presented in her book Plasticity at the Dusk of Writing and their unexpected relevance to the emergence of deep learning and artificial intelligence (AI). Malabou diagnoses the eclipse of traditional writing and deconstruction, replacing it with the concept of plasticity, a transformative and adaptive capacity. The article examines how Malabou's ideas prefigure the development of large language models like ChatGPT, which embody plasticity through their dynamic neural architectures. Despite not directly addressing AI, Malabou's work anticipates the shift toward a new form of writing and knowledge production driven by machine learning.